Práticas de letramento literário em uma turma de 7º ano - Silva, Daniely Moreira Coelho da (2019)
The practice of literary literacy, which is necessary for the formation of the subject, is, unfortunately, not a reality in most Brazilian schools. What has been witnessed in the schoolcontext is that the reading of literary texts has been predominantly a pretext for the purpose only of superficial readings, with activities that do not lead to the experience of literacy. This research is justified by recognizing, in the school environment, the little use of the literary book or the lack of articulated planning aimed at the realization of literary reading that stimulates the participation and interest of students. Given this context, this work aims to promote literary literacy from the work O Gralha, a street boy in a 7th grade elementary school class. From this perspective, associating reading with social practices can serve to form and consolidate a community of readers, since reading literature favors the reflection of social reality, contributing to the formation of an active and transformative subject. Thus, the production of a reading diary, by students, from the proposed work, can instigate the understanding, interest and participation of students during literary reading classes. Thus, this project focused mainly on the conceptions of Kleiman (2004), Soares (2005 and 2009), Paulino (2004), Paulino and Pinheiro (2004), Lajolo (2000 and 2007), Machado (2005), Cosson (2009, 2010, 2011 and 2018), Candido (1977, 1989 and 2006), Rojo (2009 and 2012), Kress and Van Leeuwen (1996 and 2006), Vieira and Silvestre (2015), Iser (1996), Jauss (1994), Zilberman (1989), Rangel (2003), Freire (2009), Rouxel (2013), Dalvi (2013), National Common Curriculum Base (2017), National Curriculum Parameters of Portuguese Language (1998), Referential Curriculum Document Ceará (2019), Suassuna (2002), Bortoni-Ricardo (2005), Bagno (1999, 2007, 2013), Bakhtin / Volochinov (1992), Marcuschi (2008), Alkmin (2001), Preti (1984, 2005, 2006), Patriota (2009), Buzzo (2003), among others. The methodology adopted was action research (THIOLLENT, 1996) with a qualitative approach. A questionnaire was applied to know the reader's profile. The Basic Sequence and Reading Circle procedures proposed by Cosson (2018), among others, were used. Data analysis theories followed the concepts of Cosson (2018) and Buzzo (2003), intertwining with the conceptions of other theorists. Thus, it was proved that the basic sequence, the reading circle and the reading diary proved to be great auxiliary tools in the process of literary literacy in schools, so working with literary reading was fundamental to make the student a more conscious subject in society, an autonomous subject who knows how to expose his voice.